RESIDUAL VOLUME OF AMPOULE-VIALS AND UNDERDOSING OF MEDICATIONS PREPARED BY A NURSING STAFF - Witkouskas, Francine Rodrigues; Magnabosco, Patricia; Alves, Luana Gabriele Souza; de Godoy, Simone; Marchi-Alves, Leila Maria (Cogitare Enfermagem, 2022)
Objective: Identify the residual volume in ampoule-vials after the preparation of injectables, associating the errors related to underdosing with the classes of drugs. Method: This is a descriptive study with a quantitative approach. Data were collected between December 2020 and September 2021, in a private outpatient service located in a Brazilian municipality in the northeast of the state of São Paulo. A total of 562 ampoule-vials of medications prepared by a nursing staff were analyzed. A form was used containing the commercial name of the medication, therapeutic class/indication, reconstitution date and time, volume used to reconstitute the medication and residual volume of each vial. The data were tabulated and analyzed using descriptive statistics and the ANOVA test. Results: theresidual volume of 462 (82.2%) ampoule-vials varied between 0.1 ml and 1.5 ml, whereas 165 (29.4%) ampoule-vials had 0.2 ml of residual volume, with a mean loss of 4.5% of the solution. There was no difference in the loss of solution between the different classes of drugs. Conclusion: The findings highlight the need for interventions to reduce failures in the medication preparation phases, with emphasis on errors associated with therapeutic underdosing.